Routledge Handbook of Sport and the Environment - McCullough, Brian; Kellison, Timothy B. (Routledge International Handbooks, 2018)
The natural environment is a central issue in both academic and wider societal discourse. The global sport industry is not immune from this discussion and has to confront its responsibility to reduce its impact on the natural environment. This book goes further than any other in surveying both the challenges and the opportunities presented to the sports industry as it engages with the sustainability agenda, exploring the various ways in which sport scholars can integrate sustainability into their research. With a multidisciplinary sweep, including management, sociology, law, events, and ethics, this is a ground-breaking book in the study of sport. Drawing on cutting-edge research, it includes over thirty chapters covering all the most important themes in contemporary sport studies such as: climate change, sustainability, and corporate social responsibility ethics, governance, and the law event management, tourism, and pollution marketing, branding, and consumer behavior the Olympics, urban development, and mega-event legacies. With contributions from world-leading researchers and practitioners from around the globe, this is the most comprehensive book ever published on sport and the environment.